Wash-free chemiluminescence imaging sensing system for portable protein assay and high-throughput screening of PCSK9 inhibitors - Yang, Ruyu; Chen, Enping; Li, Li; Wu, Liuying; Li, Huijun; Li, Ping; Zong, Chen (Sensors and actuators. B, Chemical, 2026)
The inhibition of the proprotein convertase subtilisin/kexin type 9 (PCSK9) expression can reduce the circulating low-density lipoprotein cholesterol levels and the risk of atherosclerotic cardiovascular disease. As the production of PCSK9 inhibitors continues to advance, the development of quantitative and drug screening methodologies for PCSK9 becomes increasingly essential. Herein, a novel wash-free and sensitive chemiluminescence imaging sensing system was proposed for the user-friendly, affordable and reliable immunoassay of the PCSK9 protein. By integrating the imaging system with ultra-high performance liquid chromatography quadrupole-time-of-flight mass spectrometry, a high-throughput PCSK9 inhibitor screening platform was established to facilitate the rapid identification of active ingredients in lipid-lowering traditional Chinese medicines. The imaging system enabled simultaneous quantification of PCSK9 protein in up to 96 cell lysate samples within 24 min, and presented detection limit down to 0.24 pM, without the need for separation and rinsing, only requiring straightforward mixing and pipetting, thereby enhancing both screening efficiency and accuracy. Protogracillin, methylprotodioscin, and pseudoprotodioscin were effectively screened out, exhibiting significant PCSK9 inhibitory effects and safety profiles. These findings were further validated in the HepG2 cells and hyperlipidemic mice. This work opened a valuable and viable avenue for monitoring PCSK9 levels and discovering natural small-molecule PCSK9 inhibitors, holding great potential in managing diseases associated with abnormal levels of PCSK9. [Display omitted] •Target protein-induced “signal on” were realized with chemiluminescence imaging.•The imaging system enabled wash-free and sensitive immunoassay of PCSK9 protein.•PCSK9 protein in 96 cell lysates can be detected within 24 min through simple mixing.•User-friendly and high-throughput sceening of natural PCSK9 inhibitors was achieved.